2018
DOI: 10.1002/art.40475
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of the Sacroiliac Joints Indicating Sacroiliitis According to the Assessment of SpondyloArthritis international Society Definition in Healthy Individuals, Runners, and Women With Postpartum Back Pain

Abstract: ObjectiveTo compare magnetic resonance images (MRIs) of the sacroiliac (SI) joints of healthy subjects and individuals with known mechanical strain acting upon the SI joints to those of patients with axial spondyloarthritis (SpA) and patients with chronic back pain.MethodsThree readers who had received standardized training and were blinded with regard to study group randomly scored MRIs of the SI joints of 172 subjects, including 47 healthy individuals without current or past back pain, 47 axial SpA patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
135
1
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(168 citation statements)
references
References 21 publications
(23 reference statements)
22
135
1
10
Order By: Relevance
“…Similar results were observed by de Winter et al in LBP patients, in runners, and in other healthy controls . Interestingly, de Winter and colleagues also found that BME occurring throughout the SI joints and deep lesions (depth ≥1 cm) were predominantly seen in SpA patients . The observations from these studies , together with our observations, may support the notion that local BME could be stress‐related, possibly affecting specific local “load areas” at the SI joints, while BME related to a systemic disease may cover a more extensive area and lead to structural lesions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar results were observed by de Winter et al in LBP patients, in runners, and in other healthy controls . Interestingly, de Winter and colleagues also found that BME occurring throughout the SI joints and deep lesions (depth ≥1 cm) were predominantly seen in SpA patients . The observations from these studies , together with our observations, may support the notion that local BME could be stress‐related, possibly affecting specific local “load areas” at the SI joints, while BME related to a systemic disease may cover a more extensive area and lead to structural lesions.…”
Section: Discussionsupporting
confidence: 92%
“…In a study by Weber et al that investigated physically active healthy young individuals, the authors found that, when present, BME was primarily seen at low levels and clustered topographically in distinct SI joint regions . Similar results were observed by de Winter et al in LBP patients, in runners, and in other healthy controls . Interestingly, de Winter and colleagues also found that BME occurring throughout the SI joints and deep lesions (depth ≥1 cm) were predominantly seen in SpA patients .…”
Section: Discussionsupporting
confidence: 83%
“…However, unlike SpA, joint space narrowing and ankylosis do not develop . Similar to the caution about a positive HLA‐B27 and radiographic sacroiliitis, not all bone marrow edemas on MRI are SpA as it has also been reported in healthy individuals, runners and post‐partum females …”
Section: Discussionmentioning
confidence: 86%
“…For patients with nonradiographic axial SpA, the imaging should focus on the sacroiliac joints. In interpreting MRI results, it is important to keep in mind the range and frequency of abnormalities, including bone marrow edema lesions, that may occur in individuals without axial SpA and that may not represent inflammation due to axial SpA . MRI is not recommended in patients in whom disease activity is either clearly clinically active or clinically stable, or when the results of MRI would not be expected to change treatment.…”
Section: Resultsmentioning
confidence: 99%